Resource Allocation to Upgrade the Economic Structure: Experience from South Korea's Industrial Policy - Mai, Nguyen Thi Thanh (VNU JOURNAL OF ECONOMICS AND BUSINESS, 2018)
“ Climb up” the global division of labour ladder or upgrading the economic structure is a very hard job, requiring a smart industrial policy with the capability of choosing key sectors suitably and having appropriate and effective policy to allocate resources to these sectors. When climbing up, some countries may skip several levels with the support of appropriate industrial policy, but they can slip if they try to jump too many steps at once with the rush of industrialization. Based on an analysis of the academic perspectives related to industrial policy and evidences from the sector selection process as well as the mechanism for allocating resources for the development of key South Korean industries, the paper will draw some important lessons for developing countries, including Vietnam, in order to bridge the gap with leading nations.